2008
DOI: 10.3382/ps.2008-00071
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility of a Combination of Tiamulin plus Chlortetracycline with Salinomycin in Feed During a Long-Term Co-Administration in Broilers

Abstract: The pleuromutilin antibiotic tiamulin (TIA) is known to produce a negative interaction in broilers when administered in combination with several ionophore anticoccidials such as salinomycin (SAL). Chlortetracycline (CTC), when administered simultaneously with TIA, has demonstrated a synergistic antimicrobial effect. A 35-d feeding study was conducted in cages to evaluate the interaction effect of a combination of TIA plus CTC at increasing inclusion levels when administered concurrently with SAL. A total of 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Pulse medication of broilers from 1 to 10 and 21 to 27 d with TIA at 0, 20, 30, or 50 ppm did not affect the live performance of broilers fed SAL at 60 ppm (Islam et al, 2008b). Actually, some studies showed that TIA at 20 and 30 ppm improved body weight gain and feed conversion (Islam et al 2008a;Islam et al 2008b). Considering production cost, Islam et al (2008a) found that 30 ppm of TIA produced the best economic return per unit of body weight gain.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Pulse medication of broilers from 1 to 10 and 21 to 27 d with TIA at 0, 20, 30, or 50 ppm did not affect the live performance of broilers fed SAL at 60 ppm (Islam et al, 2008b). Actually, some studies showed that TIA at 20 and 30 ppm improved body weight gain and feed conversion (Islam et al 2008a;Islam et al 2008b). Considering production cost, Islam et al (2008a) found that 30 ppm of TIA produced the best economic return per unit of body weight gain.…”
Section: Resultsmentioning
confidence: 96%
“…Actually, some studies showed that TIA at 20 and 30 ppm improved body weight gain and feed conversion (Islam et al 2008a;Islam et al 2008b). Considering production cost, Islam et al (2008a) found that 30 ppm of TIA produced the best economic return per unit of body weight gain.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some recent studies have demonstrated that the combination of pleuromutilins derivative with doxycycline had synergy effect against multidrug-resistant Acinetobacter baumannii in vitro ( Siricilla et al, 2017 ). Another investigation showed that TIA had a synergistic antimicrobial effect when in combination with chlortetracycline against Mycoplasma infection in birds ( Islam et al, 2008 ). The present study was designed to study the anti- S. aureus activity of pleuromutilins (VAL, TIA, and RET) alone and in combination with other antibiotics with different mechanism of action both in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%